KEBERADAAN DAN IMPLIKASI PRINSIP MFN DAN NT DALAM PENGATURAN HAK KEKAYAAN INTELEKTUAL DI INDONESIA - Dharmawan, Ni Ketut Supasti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 2 (2014), 2014)
The WTO – TRIPs Agreement regulates the principle of non- discrimination which must be complied by its member countries. There are two principle of non discrimination namely the principle of National Treatment ( NT ) and Most Favoured Nations principle (MFN).  This study focus to the adoption of MFN and NT principles into Intellectual Property Rights  laws of Indonesia whether it harmony with the legal system in Indonesia.   This study uses the normative legal research methods by using  conceptual approach and statute approach . The  legal materials that studies in this research  consists of the Primary Legal Materials : Act No.  19 of  2002 , Act No. No. . 15 of 2001, Act No. 14 of 2001,  as well as the TRIPs Agreement.  Secondary legal materials studied in this research are  legal text books and law journals related to NT and MFN principle in the field of Intellectual Property Rights.                                  . The results showed that the Principle of Non Discrimination System in the form of the principle of National Treatment (NT) expressly governed through  Article 3 TRIPs Agreement and the principle of Most Favoured Nations (MFN) regulated  through  Article 4 TRIPS Agreement.  As a member of WTO-TRIPs Agreement, Indonesia should comply and adopt the MFN and NT principles into IPR laws. Currently those principles exist implicitly and explicitly such as in the Act No. 19 of 2002, the Act No. 14 of 2001, and the Act No. 15 of 2001.  Although the MFN and NT principles has already adopted, it is still need more effort to implement the principle of non Discrimination, especially in the relationship between Indonesia and other unequal size countries, between developing and developed countries.
Keywords: Intellectual Property Rights; MFN; NT; TRIPS Agreement